Muslim Renaissance: Challenges in the Twenty-first Century (American Journal of Islam and Society, 2003)
The last three decades have brought profound changes to how we look atthe funadmental notions that define the modern world, such as culture, ideology,religion, reform, and progress. A drastic shift from a bipolar worlddefined by the rivalry betweeen the liberal West and the communist bloc inthe 1980s, to a globalization intent upon breaking both market and culturalbarriers in the 1990s, to a new form of polarization driven by religious andcultural exclusivism at the turn of the twenty-first century. Not only hascommunism succumbed and disappeared as a credible sociopolitical force,but liberalism itself is in retreat even in the United States, the most liberalsociety of all, giving way to a new tide of conservatism.Evidently, the tide of conservatism seeking to replace both progressiveand revolutionary movements does not bring new hopes of a betterfuture; rather, it seems to be bent on reclaiming old postures of selfrighteousnessand ethnicity that fueled hatred, international hostility, andwars. Secularist idedologies are giving rise to religious ideologies, as canbe seen clearly in almost every culture, whether in the United States,India, or Turkey.In Muslim societies, religious conservatism has cloaked the Islamicreform movement’s forward vision and threatens to roll back its achievements.The reform movement also has been suppressed by the overbearingpolitical regimes ruling the Muslim world. Many people questionwhether an Islamic renaissance – or a renaissance based on Islamic values– is even posible and, if so, how does it relate to rising conservativeand declining modernist ideologies? ...